2022
DOI: 10.1016/j.ijantimicag.2021.106516
|View full text |Cite
|
Sign up to set email alerts
|

High-dose ivermectin for early treatment of COVID-19 (COVER study): a randomised, double-blind, multicentre, phase II, dose-finding, proof-of-concept clinical trial

Abstract: High concentrations of ivermectin demonstrated antiviral activity against SARS-CoV-2 in vitro . Aim of this study was to assess safety and efficacy of high-dose ivermectin in reducing viral load in individuals with early SARS-CoV-2 infection. Randomised, double-blind, multicentre, phase II, dose-finding, proof-of-concept clinical trial. Participants: adults recently diagnosed with asymptomatic/oligosymptomatic SARS-CoV-2 infection, providing informed consent. Exclusion criteria: pregnant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 31 publications
2
38
0
3
Order By: Relevance
“…These studies were included in a number of systematic reviews and meta-analyses that reported the beneficial effect of this medication [ 14 , 16 18 ]. Furthermore, recent RCTs have shown that ivermectin is ineffective in the treatment of COVID-19 [ 19 , 20 ]. Since the beginning of the pandemic, all of these have caused controversy regarding the possible effects of this drug.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies were included in a number of systematic reviews and meta-analyses that reported the beneficial effect of this medication [ 14 , 16 18 ]. Furthermore, recent RCTs have shown that ivermectin is ineffective in the treatment of COVID-19 [ 19 , 20 ]. Since the beginning of the pandemic, all of these have caused controversy regarding the possible effects of this drug.…”
Section: Introductionmentioning
confidence: 99%
“…There are some concerns regarding the accuracy of the results of previous studies that should be addressed. The most important concerns are several retractions of clinical trials [ 21 ], the availability of inaccurate or outdated meta-analyses [ 14 , 22 , 23 ], and three RCTs recently published in 2022 [ 19 , 20 , 24 ] which their final results were not included in previous meta-analyses. Considering these issues, we set out to conduct a comprehensive systematic review and meta-analysis of current peer-reviewed randomized controlled trials to assess the possible effect of ivermectin in patients with COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…No additional articles were retrieved from the reference lists of the included studies. Of the 21 included studies, 04 were available as preprints upon the time of submission of the present study [45][46][47][48].…”
Section: Search Resultsmentioning
confidence: 99%
“…In nine of them, the registration was done after the beginning of recruitment, in one of them the recruitment period was not mentioned, and the protocols of three studies could not be retrieved for the registration date to be checked. In eight studies, there were amends in the protocol after the registration [19,45,47,48,49,50,51,52]. * The nal sample for adverse effects is different to the nal sample for our primary outcomes ** This arm was not included in the meta-analysis 1 Lopinavir/ritonavir.…”
Section: Study and Patients' Characteristicsmentioning
confidence: 99%
“…Whether this drug might have clinical efficacy at lower doses remains debated. The recommendation of the WHO suggests that it is currently advisable to refrain from administrating ivermectin for the treatment of COVID-19 outside clinical trials [ 156 ]. These studies are summarized in Table 4 .…”
Section: Recent Clinical Studiesmentioning
confidence: 99%